Highly active mononuclear NAC-gold(I) catalysts - Blanco Jaimes, Maria Camila; Böhling, Constantin R. N.; Serrano‐Becerra, Juan Manuel; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2013)
One gold is enough: Mononuclear, homogeneous gold catalysts displayed excellent catalytic activity on the order of that previously reported for gold nanoparticle catalysts and surface-bound gold complexes. In the model synthesis of spiro compounds (see picture) extremely high turnover numbers were achieved with only 0.000001 mol % of a silsesquioxane-substituted catalyst.
Gesehen am 24.03.2021